Research on Liquid Flow Resistance in Flow and Centrifugal Extraction Reactors - MĄCZAK, Jędrzej; SAMOILENKO, Dmytro; MAKOWSKI, Michal; KNAP, Lech (Engineering Transactions, 2025)
This paper presents research that formed the basis for the development of a low-temperature centrifugal extraction reactor. This reactor is used to obtain medicinal substances from herbs, where key parameters include extraction time, temperature, and the velocity of the solvent that flows through the dried herbs. An important parameter for performing simulation studies was the assessment of the medium flow characteristics through the dried medicinal herb material. For this purpose, a flow reactor was developed and tested.The first part of the paper discusses the results of numerical and experimental studies on liquid flow through the extraction reactor. This part of the work was carried out in order to determine the parameters related to the resistance of liquid flow through dried medicinal herbs. This resistance of the liquid flow through the herbs affects the limitation of its velocity and has a direct impact on the efficiency of the process. In the second part of the paper, the results obtained from the flow reactor experiments were used for numerical investigations of the centrifugal extractor drum.